PENGEMBANGAN MEDIA BARANG BEKAS UNTUK MENINGKATKAN AKTIVITAS PEMBELAJARAN IPA SISWA KELAS IV SD NEGERI SEUMANTOK KECAMATAN PANTE CEUREUMEN KABUPATEN ACEH BARAT - Nurjannah; Azianur Mauliza; Dian Kristanti; Agus Kistian (LPPM Universitas Cipta Mandiri, 2024)
This research aims to describe the development of second-hand media to improve science learning activities for fourth grade students at SD Negeri Seumantok. This type of research is development, namely: Research and Development (R&D). The subjects in this research were 19 grade IV students at Seumantok State Elementary School. Data collection techniques include: observation and tests. Based on the results of the research, it was concluded that the development of used media to improve science learning activities for fourth grade students at SD Negeri Seumantok resulted in validation of an average score of 4.5 and the learning process carried out had gone well in accordance with the learning scenario, the results of observations from the implementation of categorized learning good, and the average final score for each result has increased so that the average percentage of classical student scores that achieve a score of more than or equal to 65 is 70. This is in accordance with the Minimum Completeness Standards (SKM) and second-hand media can help the teacher explains the material being taught and the students will not feel bored while learning so that a pleasant learning atmosphere is created, even though it is only in the form of used goods but is useful in learning.